Analisis Pesan Dark jokes dalam Konten Bintang Emon Tentang Kasus Penyiraman Air Keras Novel Baswedan di Media Sosial Instagram - Mointi, Moh. Fahriwan; Thomas, Abdul Wahab; Tamu, Yowan; Kurnia, Moh. Mirza (JAMBURA JURNAL ILMU KOMUNIKASI, 2024)
Dark jokes refer to a style of comedy that often focuses on subjects considered taboo or sentistive by most people. In Indonesiaan’s entertainment industry, one stand up comedian known by frequently using this style is Bintang Emon. In every piece of content, he creates and publishes through his social media accounts, particularly Intagram, Bintang consistently incorporates dark jokes that entertaint his audience or spark controversy. An example of this is his content that garnered significant attention when he criticized the court’s decision regarding the Novel Baswedan acid attack case. This research aims to analyze messages behind the dark jokes in Bintang Emon’s Instagram content related to the acid attack on Novel Baswedan. The research employs a qualitative approach and analyzes that content using Andrik Porwasito’s four stages of message analisys. The results indicate that Bintang Emon aims to convery a critical message using humor, particularly through satire, wordplay, and absurd analogies In relation to the case.